Anatomy of an electoral tsunami - Lim, Teck Ghee; Thayaparan, S.; Netto, Terence (Strategic Information and Research Development Centre, 2018)
'A magnificent tour de force of Malaysian politics leading up to the 9th May tsunami by three of our nation's most prolific and respected commentators. Together, they took on the political establishment with courage, determined to speak truth to power as they saw it. We owe men like these a debt of gratitude for keeping hope alive during some of our nations darkest moments and for helping us to better understand the personalities and the issues that were shaping political discourse at a critical time in our nation's history.' -Dennis Ignatius